Application of Quality Assurance Strategies in Diagnostics and Clinical Support Services in Iranian Hospitals - Asgar Aghaei Hashjin; Dionne Kringos; Hamid Ravaghi; Jila Manoochehri; Hassan Abolghasem Gorji; Niek Klazinga (Kerman University of Medical Sciences, 2015)
Background Iran has a widespread diagnostics and clinical support services (DCSS) network that plays a crucial role in providing diagnostic and clinical support services to both inpatient and outpatient care. However, very little is known on the application of quality assurance (QA) policies in DCSS units. This study explores the extent of application of eleven QA strategies in DCSS units within Iranian hospitals and its association with hospital characteristics. Methods A descriptive cross-sectional study was conducted in 2009/2010. Data were collected from 554 DCSS units among 84 hospitals. Results The average reported application rate for the QA strategies ranged from 57%-94% in the DCSS units. Most frequently reported were checking drugs expiration dates (94%), pharmacopoeia availability (92%), equipment calibration (87%) and identifying responsibilities (86%). Least reported was external auditing of the DCSS (57%). The clinical chemistry and microbiology laboratories (84%), pharmacies, blood bank services (83%) reported highest average application rates across all questioned QA strategies. Lowest application rates were reported in human tissue banks (50%). There was no significant difference between the reported application rates in DCSS in the general/specialized, teaching/research, nonteaching/research hospitals with the exception of pharmacies and radiology departments. They reported availability of a written QA plan significantly more often in research hospitals. Nearly all QA strategies were reported to be applied significantly more often in the DCSS of Social Security Organization (SSO) and private-for-profit hospitals than in governmental hospitals. Conclusion There is still room for strengthening the managerial cycle of QA systems and accountability in the DCSS in Iranian hospitals. Getting feedback, change and learning through application of specific QA strategies (eg, external/internal audits) can be improved. Both the effectiveness of QA strategies in practice, and the application of these strategies in outpatient DCSS units require further policy attention.